Super-hydrophobic coating material and preparation method thereof
By constructing nanostructures on the surface of millimeter-scale metal powder particles and chemically modifying, modified milli-nano structure metal-based particles are prepared, and superhydrophobic coating materials are formed in combination with polymer binders, which solves the problem of superhydrophobic coating in the prior art The problem of poor mechanical properties of the layer has achieved efficient superhydrophobic and physical mechanical properties improvements, and is suitable for large-area industrial applications.
Patent Information
- Application Number
- CN202411607101.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The mechanical properties of existing superhydrophobic coatings are poor and difficult to be suitable for large-area industrial applications.
The nanostructure was constructed on the surface of millimeter-scale metal powder particles by acid etching, and modified by chemical modification method to prepare modified milli-nano structure metal-based particles, and combined with polymer binder to form a superhydrophobic coating material.
While achieving the superhydrophobic properties of the coating, it significantly improves its physical and mechanical properties, including impact resistance and flexibility, ensuring that the coating has good structural stability in large-area applications.
Smart Images

Figure CN119463706A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of super hydrophobic coatings, and in particular to a super hydrophobic coating material and a preparation method thereof. Background Art
[0002] Superhydrophobic coatings have broad application prospects in the fields of construction, energy, communications, and electricity due to their excellent self-cleaning properties, drag reduction in fluid transport, anti-icing, and corrosion resistance. For example, in the process of oil extraction, the emergence of superhydrophobic materials provides a new technical approach for oil-water separation. In the power supply system, the anti-condensation properties of the superhydrophobic surface can effectively extend the service life of the transmission line, so that the transmission line can be powered normally in an extremely cold environment. In industrial production, superhydrophobic coatings can be effectively used to prevent oil and dust on the glass surface, and can also be used for waterproofing and anti-fogging of optical instrument lenses. Metal materials coated with superhydrophobic coatings have excellent corrosion resistance, and their service life is greatly extended under the same service conditions.
[0003] Due to the unique properties and functions of super-hydrophobic coatings, the precise construction of super-hydrophobic coatings has become a current research hotspot. In the past 20 years, a large number of scholars have conducted in-depth explorations on super-hydrophobic coatings. The results show that constructing a "concave-convex micro-nano" structure with a lotus leaf-like surface is the key to achieving super-hydrophobic properties of the coating. At present, a large number of super-hydrophobic coating construction methods have emerged, such as self-assembly, spraying, phase separation, sol-gel, electrochemical deposition, and the like. Among them, the spraying method is favored in the construction of super-hydrophobic coatings because of its simple operation, no precision instruments, low cost, and easy industrialization. However, in order to construct a micro-nano structure on the surface of the coating, which is a key factor in achieving super-hydrophobic properties, a large amount of nano-pigments, such as nano-silicon dioxide, carbon nanowires, zinc oxide whiskers, etc., need to be doped in the coating system, and the pigment volume concentration is significantly higher than the critical value. The low resin content causes the coating to "fall powder" due to the difficulty in coating all the pigments, and it is easy to lose super-hydrophobicity due to damage such as scratching and impact. For example, patent CN111334136A discloses a long-lasting oil-proof coating, which simply combines a resin binder with a nanoparticle solution and also does not have high wear resistance. Therefore, there is still no super-hydrophobic coating that can be applied industrially on a large scale. Summary of the invention
[0004] The purpose of the invention is to provide a super-hydrophobic coating material and a preparation method thereof, so as to solve the problem that the existing super-hydrophobic coating has poor mechanical properties and is not suitable for large-scale industrial applications.
[0005] The present invention is achieved by providing a method for preparing a super hydrophobic coating material, the method comprising the following steps:
[0006] Step 1: Prepare modified milli-nanostructured metal-based particles: Use millimeter-sized metal powder particles as base particles, use a mixed solution of water, hydrochloric acid and hydrofluoric acid in a volume ratio of (80-100): (8-10): 1 to etch the metal-based particles, construct a nanostructure on the surface of the base particles, and then add them to a low surface energy solution for chemical modification;
[0007] Step 2: The material obtained in step 1 is combined with an adhesive to obtain a super-hydrophobic coating material.
[0008] The present invention uses millimeter-level metal powder particles as matrix particles, uses acid etching to build nanostructures on its surface, builds nanostructures on millimeter-level particle surfaces to prepare milli-nanostructure particles, and is modified by chemical modification, prepares modified second-order milli-nanostructure metal-based particles, and uses this as a functional material and a polymer adhesive to mix film-forming, while realizing the super-hydrophobic performance of the coating, it can also significantly improve its physical and mechanical properties. And the present invention has a strong chemical interaction force between the nanostructure constructed in situ on the surface of millimeter-level particles and the overall particle, is not easy to destroy separation from each other, has good structural stability, and this is another advantage of the super-hydrophobic coating prepared by the present invention.
[0009] A further technical solution of the present invention is: in step 1, the etching time is 10-60 minutes, and after etching, the particles are washed with deionized water and dried for later use. The mixed solution of the present invention is highly efficient in acid etching and can etch a nanometer-scale surface layer on millimeter-scale metal powder particles.
[0010] A further technical solution of the present invention is that the mass of the metal-based particles, the volume of the mixed solution and the volume ratio of the low surface energy solution are: (2-5) g: (94-125) mL: (12-20) mL. The low surface energy solution in the present invention fully modifies the active sites on the surface of the metal particles. Moreover, the adhesive can adhere to the metal particles without covering the metal particles.
[0011] A further technical solution of the present invention is that the millimeter-sized metal powder particles in step 1 include at least one of millimeter-sized aluminum powder particles, millimeter-sized copper powder particles and millimeter-sized zinc powder particles. These metal powder particles are active metals and are easily etched by acid to form a nanometer surface layer.
[0012] A further technical solution of the present invention is: the low surface energy solution comprises at least one of a n-hexane solution containing trichloro 1H, 2H, 3H heptadecafluorodecylsilane, an ethanol solution containing palmitic acid, and an ethanol solution containing stearic acid.
[0013] A further technical solution of the present invention is: in step 1, the millimeter-sized metal powder particles are cleaned with deionized water and anhydrous ethanol respectively, and then acid-etched.
[0014] A further technical solution of the present invention is: the chemical modification in step 1 is: adding the etched metal-based particles into a low surface energy solution and letting it stand for 12 hours. The superhydrophobic effect exceeds that of other low surface energy solutions.
[0015] A further technical solution of the present invention is: the adhesive in step 2 is AB glue, AB glue is mixed in a mass ratio of 1:1, and the coating thickness is 2mm to 3mm to obtain a film, the material obtained in step 1 is dispersed on the surface of the film, embedded in the film and cured for 24h to obtain a super hydrophobic coating material. It is convenient to operate and easy to prepare.
[0016] A further technical solution of the present invention is that the mass ratio of the material obtained in the step 1 to the adhesive is: (1.5-4):1.
[0017] The present invention also provides a super-hydrophobic coating material, and the super-hydrophobic coating material is prepared by the preparation method.
[0018] Inspiringly, despite the extremely low resin content of building exterior wall mortar paint, the exposed and protruding sand and gravel particles can still bond with each other to form a continuous overall coating and firmly adhere to the wall surface. This is due to the large size and low specific surface area of millimeter-level sand and gravel particles. Even at high pigment volume concentrations, there is still excellent bonding between particles and between particles and substrates, thus forming a hard overall coating. Therefore, if nanostructures can be constructed on the surface of millimeter-level particles, milli-nanostructured particles can be prepared, and these can be used as functional pigments and mixed with polymers to form a film, it is expected that while achieving super-hydrophobic properties of the coating, its physical and mechanical properties can also be significantly improved.
[0019] Beneficial effects of the present invention: the present invention uses millimeter-level metal powder particles as matrix particles, uses acid etching to construct nanostructures on their surfaces, constructs nanostructures on the surfaces of millimeter-level particles to prepare milli-nanostructure particles, and modifies them by chemical modification to prepare modified second-order milli-nanostructure metal-based particles, and uses this as a functional material and a polymer adhesive to form a film, while achieving the super-hydrophobic performance of the coating, it can also significantly improve its physical and mechanical properties. And the present invention has a strong chemical interaction force between the nanostructure constructed in situ on the surface of millimeter-level particles and the overall particles, which is not easy to destroy and separate from each other, and has good structural stability, which is another advantage of the super-hydrophobic coating prepared by the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a flow chart of a method for preparing a super hydrophobic coating material provided by the present invention;
[0021] Figure 2 The surface microscopic morphology and chemical composition of the milli-nanostructured aluminum-based particles obtained in Example 1 provided by the present invention;
[0022] Figure 3 This is a test diagram of the hydrophobic performance of the super-hydrophobic coating material obtained in Example 1 provided by the present invention;
[0023] Figure 4 This is a test result diagram of the flexibility and impact resistance of the super-hydrophobic coating material obtained in Example 1 provided by the present invention. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0025] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0026] The present invention provides a method for preparing a super-hydrophobic coating material, the method comprising the following steps:
[0027] Step 1: Prepare modified milli-nanostructured metal-based particles: Use millimeter-sized metal powder particles as base particles, use a mixed solution of water, hydrochloric acid and hydrofluoric acid in a volume ratio of (80-100): (8-10): 1 to etch the metal-based particles, construct a nanostructure on the surface of the base particles, and then add them to a low surface energy solution for chemical modification;
[0028] Step 2: The material obtained in step 1 is combined with an adhesive to obtain a super-hydrophobic coating material.
[0029] Furthermore, in the step 1, the etching time is 10 min-60 min, and after etching, the surface is washed with deionized water and dried for later use.
[0030] Furthermore, the mass of the metal-based particles, the volume of the mixed solution and the volume ratio of the low surface energy solution are: (2-5) g: (94-125) mL: (12-20) mL.
[0031] Furthermore, the millimeter-sized metal powder particles in step one include at least one of millimeter-sized aluminum powder particles, millimeter-sized copper powder particles, and millimeter-sized zinc powder particles.
[0032] Furthermore, the low surface energy solution includes at least one of a n-hexane solution containing trichloro 1H, 2H, 3H heptadecafluorodecylsilane, an ethanol solution containing palmitic acid, and an ethanol solution containing stearic acid.
[0033] Furthermore, in step 1, the millimeter-sized metal powder particles are cleaned with deionized water and anhydrous ethanol respectively, and then acid-etched.
[0034] Furthermore, the chemical modification in step 1 is as follows: adding the etched metal-based particles into a 1% by mass 1H, 2H, 3H heptadecafluorodecylsilane trichloride n-hexane solution and leaving it to stand for 12 hours.
[0035] Furthermore, in the step 2, the adhesive is AB glue, which is mixed in a mass ratio of 1:1 and coated with a thickness of 2 mm to 3 mm to obtain a film, and the material obtained in step 1 is dispersed on the surface of the film, embedded in the film and cured for 24 hours to obtain a super-hydrophobic coating material.
[0036] Furthermore, the mass ratio of the material obtained in the step 1 to the adhesive is: (1.5-4):1.
[0037] Embodiment 1:
[0038] A preparation method of a super-hydrophobic coating material comprises the following steps: washing 2 g of millimeter-sized aluminum-based particles with deionized water and anhydrous ethanol respectively; etching the aluminum-based particles with 111 mL of a mixed solution prepared with water, hydrochloric acid and hydrofluoric acid (volume ratio of 100:10:1) for 35 min, washing with deionized water after etching, and drying for standby use; adding the etched aluminum-based particles to 15 mL of a 1% by mass 1H, 2H, 3H heptafluorodecylsilane trichlorohydrate n-hexane solution, standing for modification for 12 h, and obtaining aluminum-based particles with a milli-nano structure modified with fluorosilane.
[0039] Then, a super-hydrophobic coating is constructed with low surface energy milli-nanostructured aluminum-based particles: component A and component B are evenly mixed in a mass ratio of 1:1 to obtain AB glue, and the AB glue is applied to the polished tinplate surface to prepare a glue film with a thickness of 2 to 3 mm; according to the mass ratio of fluorosilane-modified milli-nanostructured aluminum-based particles to AB glue of 2:1, the fluorosilane-modified milli-nanostructured aluminum-based particles are evenly dispersed on the surface of the glue film, and lightly pressed into the glue film, and cured for 24 hours to obtain a super-hydrophobic coating material.
[0040] Embodiment 2:
[0041] A preparation method of a super-hydrophobic coating material comprises the following steps: 3 g of millimeter-sized copper-based particles are respectively cleaned with deionized water and anhydrous ethanol; the copper-based particles are etched for 55 min with 111 mL of a mixed solution prepared with water, hydrochloric acid and hydrofluoric acid (volume ratio of 100:10:1), and after etching, the copper-based particles are cleaned with deionized water and dried for standby use; the etched copper-based particles are added to 12 mL of a 1% by mass 1H, 2H, 3H heptafluorodecyl silane trichloride n-hexane solution, and the solution is allowed to stand for modification for 12 h to obtain fluorosilane-modified milli-nanostructured copper-based particles.
[0042] Then, a super-hydrophobic coating is constructed with low surface energy milli-nanostructured copper-based particles: component A and component B are evenly mixed in a mass ratio of 1:1 to obtain AB glue, and the AB glue is applied to the polished tinplate surface to prepare a glue film with a thickness of 2 to 3 mm; according to the mass ratio of fluorosilane-modified milli-nanostructured copper-based particles to AB glue of 2:1, the fluorosilane-modified milli-nanostructured copper-based particles are evenly dispersed on the surface of the glue film, and lightly pressed into the glue film, and cured for 24 hours to obtain a super-hydrophobic coating material.
[0043] Embodiment three:
[0044] A preparation method of a super-hydrophobic coating material comprises the following steps: 4 g of millimeter-sized zinc-based particles are respectively cleaned with deionized water and anhydrous ethanol; the zinc-based particles are etched for 45 min with 111 mL of a mixed solution prepared with water, hydrochloric acid and hydrofluoric acid (volume ratio of 100:10:1), and after etching, the zinc-based particles are cleaned with deionized water and dried for standby use; the etched zinc-based particles are added to 20 mL of a 1% by mass 1H, 2H, 3H heptafluorodecylsilane trichlorohydrate n-hexane solution, and the solution is allowed to stand for modification for 12 h to obtain fluorosilane-modified milli-nanostructured zinc-based particles.
[0045] Then, a super-hydrophobic coating is constructed with low surface energy milli-nanostructured zinc-based particles: component A and component B are evenly mixed in a mass ratio of 1:1 to obtain AB glue, and the AB glue is applied to the polished tinplate surface to prepare a glue film with a thickness of 2 to 3 mm; according to the mass ratio of fluorosilane-modified milli-nanostructured zinc-based particles to AB glue of 2:1, the fluorosilane-modified milli-nanostructured zinc-based particles are evenly dispersed on the surface of the glue film, and lightly pressed into the glue film, and cured for 24 hours to obtain a super-hydrophobic coating material.
[0046] Embodiment 4:
[0047] A preparation method of a super-hydrophobic coating material comprises the following steps: washing 2 g of millimeter-sized aluminum-based particles with deionized water and anhydrous ethanol respectively; etching the aluminum-based particles with 94 mL of a mixed solution prepared with water, hydrochloric acid and hydrofluoric acid (volume ratio of 85:8:1) for 35 min, washing with deionized water after etching, and drying for standby use; adding the etched aluminum-based particles into 15 mL of a 1% by mass 1H, 2H, 3H heptafluorodecylsilane trichloro n-hexane solution, standing for modification for 12 h, and obtaining aluminum-based particles with a milli-nano structure modified with fluorosilane.
[0048] Then, a super-hydrophobic coating is constructed with low surface energy milli-nanostructured aluminum-based particles: component A and component B are evenly mixed in a mass ratio of 1:1 to obtain AB glue, and the AB glue is applied to the polished tinplate surface to prepare a glue film with a thickness of 2 to 3 mm; according to the mass ratio of fluorosilane-modified milli-nanostructured aluminum-based particles to AB glue of 2:1, the fluorosilane-modified milli-nanostructured aluminum-based particles are evenly dispersed on the surface of the glue film, and lightly pressed into the glue film, and cured for 24 hours to obtain a super-hydrophobic coating material.
[0049] Embodiment five:
[0050] A preparation method of a super-hydrophobic coating material comprises the following steps: washing 2 g of millimeter-sized aluminum-based particles with deionized water and anhydrous ethanol respectively; etching the aluminum-based particles with 105 mL of a mixed solution prepared with water, hydrochloric acid and hydrofluoric acid (volume ratio of 95:9:1) for 35 min, washing with deionized water after etching, and drying for standby use; adding the etched aluminum-based particles into 15 mL of a 1% by mass 1H, 2H, 3H heptafluorodecylsilane trichlorohydrate n-hexane solution, standing for modification for 12 h, and obtaining aluminum-based particles with a milli-nano structure modified with fluorosilane.
[0051] Then, a super-hydrophobic coating is constructed with low surface energy milli-nanostructured aluminum-based particles: component A and component B are evenly mixed in a mass ratio of 1:1 to obtain AB glue, and the AB glue is applied to the polished tinplate surface to prepare a glue film with a thickness of 2 to 3 mm; according to the mass ratio of fluorosilane-modified milli-nanostructured aluminum-based particles to AB glue of 2:1, the fluorosilane-modified milli-nanostructured aluminum-based particles are evenly dispersed on the surface of the glue film, and lightly pressed into the glue film, and cured for 24 hours to obtain a super-hydrophobic coating material.
[0052] Comparative Example 1:
[0053] A method for preparing a super-hydrophobic coating material, the steps are: 2g of millimeter-sized aluminum-based particles are washed with deionized water and anhydrous ethanol respectively; the aluminum-based particles are etched for 35 minutes with 112mL of a mixed solution prepared with water and hydrochloric acid (volume ratio is 15:1), and then washed with deionized water after etching, and dried for use; the etched aluminum-based particles are added to 15mL of a 1% trichloro 1H, 2H, 3H heptafluorodecylsilane n-hexane solution, and allowed to stand for modification for 12 hours to obtain fluorosilane-modified aluminum-based particles. After testing, the surface layer of the aluminum-based particles is not nanoscale.
[0054] Component A and component B are mixed evenly in a mass ratio of 1:1 to obtain AB glue, and the AB glue is applied to the polished tinplate surface to prepare a film with a thickness of 2 to 3 mm; according to the mass ratio of fluorosilane-modified aluminum-based particles to AB glue of 2:1, the fluorosilane-modified aluminum-based particles are evenly dispersed on the surface of the film, and lightly pressed into the film, and cured for 24 hours to obtain a coating material. The coating material does not have superhydrophobicity.
[0055] Comparative Example 2:
[0056] A method for preparing a super-hydrophobic coating material comprises the following steps: washing 2 g of millimeter-sized aluminum-based particles with deionized water and anhydrous ethanol respectively; etching the aluminum-based particles with 111 mL of a mixed solution prepared with water, hydrochloric acid and sulfuric acid (volume ratio of 100:10:1) for 35 min, washing with deionized water after etching, and drying for later use; adding the etched aluminum-based particles to 15 mL of a 1% hexane solution of trichloro-1H, 2H, 3H heptafluorodecylsilane, standing for modification for 12 h, and obtaining fluorosilane-modified aluminum-based particles. After testing, it was found that there was no nanostructure on the surface of the aluminum-based particles.
[0057] Component A and component B are mixed evenly in a mass ratio of 1:1 to obtain AB glue, and the AB glue is applied to the polished tinplate surface to prepare a film with a thickness of 2 to 3 mm; according to the mass ratio of fluorosilane-modified aluminum-based particles to AB glue of 2:1, the fluorosilane-modified aluminum-based particles are evenly dispersed on the surface of the film, and lightly pressed into the film, and cured for 24 hours to obtain a coating material. The coating material does not have superhydrophobicity.
[0058] Performance Test:
[0059] The surface morphology and chemical composition of the aluminum-based particles modified with milli-nano structures obtained in Example 1 of the present invention were analyzed: a field emission scanning electron microscope (ZEISS Sigma300SEM, Germany) equipped with a Smartedx spectrometer (EDS) was used to characterize the microstructure and surface elemental composition of the particles. During the test, the sample was imaged using a SE2 secondary electron detector at an accelerating voltage of 3 kV. The EDS spectrum was tested under the conditions of an accelerating voltage of 15 kV and a working distance of 8.5 mm. At the same time, an X-ray photoelectron spectrometer (XPS) equipped with a monochromatic Al Kα source (hν=1486.6 eV) was used to analyze the chemical composition of the particle surface at room temperature. During the test, the power was 12 kV×6 mA and the spot size was 400 μm.
[0060] The results are as follows Figure 2 As shown, Figure 2 a~c show the surface micromorphology of acid-etched aluminum particles of different sizes after modification. It can be seen that a large number of uneven pore structures and gap groove structures appear on the surface of the modified particles. The gap width is tens of nanometers to several microns, the length is several microns to tens of microns, and the depth is several nanometers to several microns. This is caused by a strong chemical reaction between the acid and the aluminum-based particles during the etching process, and the release of gas, which causes the surface of the particles to dissolve and corrode. At the same time, it was also found that the surface of the particles was covered with a large amount of nanoscale white granular substances. EDS analysis was performed on it, and the results are as follows Figure 2 As shown in d-g, it is found that the three elements F, Si and Cl are evenly distributed on the surface of aluminum-based particles, and their mass fractions on the particle surface are 81.23%, 15.09% and 3.69% respectively. Figure 2 h). This is because during the modification process, trichloro-1H,2H,3H heptafluorodecylsilane (FDTS) is hydrolyzed and reacts with the hydroxyl groups on the surface of the aluminum-based particles to attach to the surface. The schematic diagram of the reaction principle is shown in Figure 2 i. However, the hydroxyl density on the surface of aluminum particles is limited, so part of the FDTS self-assembles during the modification process, resulting in the agglomeration of FDTS, thereby forming white granular substances on the surface of the particles. Analysis of SEM and EDS images shows that this experiment has successfully constructed fluorinated siliconized second-order milli-nanostructured aluminum-based particles.
[0061] The super hydrophobic coating material obtained in Example 1 was characterized:
[0062] Hydrophobicity: The static water contact angle and dynamic water contact angle of the coating were characterized by an optical water contact angle tester (Lauda Scientific LSA100, Germany). The final static water contact angle was represented by the average value of the test results of four different areas of the coating.
[0063] The results are as follows Figure 3 As shown by Figure 3 It can be seen from a that the water droplets are distributed in a spherical shape on the coating surface. The water contact angles in four different areas are 153.8°, 153°, 152.2° and 153.1° respectively, with an average of 153°, which is higher than the critical value of 150°, achieving super hydrophobic performance. In order to determine the hydrophobic stability of the coating, this experiment also tested the dynamic water contact angle of the coating. The results are shown in Figure 3 As shown in Fig. b, it can be seen that the water contact angle was maintained at about 153.1° during the test, which was in a stable state and had good hydrophobic stability. In addition, to further verify the anti-wetting performance of the coating, this study also tested the wetting of crystal violet solution, methyl orange solution, methylene blue solution, mud slurry, NaCl solution, cola, tea, and water on the coating surface. The results are shown in Figure 3 c It can be seen that all droplets exist in a spherical shape on the coating surface, and can roll as the coating tilts, showing super strong anti-wetting performance. The above results show that a super-hydrophobic coating with stable performance is prepared using milli-nano structure particles as functional pigments. This is because the coating surface constructed by milli-nano structure aluminum-based particles has a uniform "micro-nano" structure, which has a strong ability to hold air, thereby forming a non-polar air layer. The water droplets falling on its surface are in a hydrophobic environment, and are condensed into a spherical liquid under the action of surface tension, forming a water contact angle greater than 150° with the coating surface, and can roll down at a smaller angle. Stable super-hydrophobic performance will provide important guarantees for the coating to achieve self-cleaning, anti-icing, anti-corrosion and other functions.
[0064] Impact resistance: According to GB / T1732-1993 Determination of impact resistance of paint film, the impact resistance of the coating is characterized by a paint film impact tester (BGD 302, China). During the test, the test plate is placed flat on an iron sticker with the painted surface facing up, and a heavy hammer is made to impact the coating from a certain height in a free fall manner. The impact point is observed for cracks, leakage, etc., and its hydrophobicity is tested.
[0065] The results are as follows Figure 4 As shown, the coating of Example 1 is placed on a shaft with a diameter of 2 mm and bent 180° around the shaft. There is no crack or peeling phenomenon in the bent cross section of the coating. Figure 4As shown in a, it shows that the flexibility reaches 2mm. Since it is difficult for water droplets to stay on the curved interface, its hydrophobicity is tested by the water drop residue. When a water droplet is dropped on the curved cross section, the droplet is deformed by the impact and then rebounds and falls. There is no adsorption residue on the surface, indicating that the curved surface of the coating still has excellent hydrophobicity and the coating has strong anti-bending ability.
[0066] The surface of super-hydrophobic coating is usually composed of micro-nano secondary rough structure, which helps to achieve super-hydrophobic effect, but this micro-nano structure formed by simple blending and stacking of nanoparticles has low resin content and loose pigment connection, which is easily damaged by physical impact and loses super-hydrophobicity. Impact resistance refers to the ability of coating to withstand rapid deformation under high-speed gravity without cracking or falling off from the metal substrate. The test results are as follows: Figure 4 As shown in Figure b. Under the impact of heavy hammers at different heights, there are no cracks or peeling marks on the coating surface. This is due to the large overall size of the aluminum particles. Under the action of the resin, the particles have better bonding effects between the particles and between the particles and the substrate. They are not easy to be destroyed and separated from each other, and have good structural stability. The hydrophobicity of the coating is judged by the motion state of the water droplets at the impact dent. The results show that the water droplets can easily roll over the "pit" surface formed by the impact of 10Kg·cm and 15Kg·cm without leaving any traces. On the "pit" surface formed under the impact strength of 20Kg·m, there is resistance when the water droplets roll over the "pit", and a small amount of liquid remains on its surface. Therefore, the impact resistance of the coating is 15Kg·m, which is good impact resistance. This is because the nanostructure constructed in situ on the surface of the millimeter-level particles has a strong chemical interaction force with the overall particles. When impacted by the outside world, it can still maintain a good microscopic rough structure, so that its surface still has excellent superhydrophobic properties. The low specific surface area of large-sized particles brings about a better bonding effect, which together gives the coating good mechanical properties. The good physical and mechanical properties of the coating lay a solid foundation for its outdoor application.
[0067] Flexibility: According to GB / T1731-2020 "Determination of paint film flexibility", a paint film flexibility tester (BGD560, China) is used to evaluate the bending resistance of the coating. With the coating surface facing up, use both hands to press the coating sample tightly onto a shaft rod of the specified diameter of the flexibility tester. Bend the test plate around the shaft rod at a steady speed within 2 to 3 seconds to observe whether the paint film has mesh, cracks, and peeling. Bend the aluminum particle coating 180° around the shaft rod with a diameter of 2 mm. There is no crack or peeling on the bent section of the coating. Figure 4 As shown in a, it shows that the flexibility reaches 2mm.
[0068] The present invention uses millimeter-level aluminum powder particles as matrix particles, uses acid etching to build nanostructure on its surface, builds nanostructure on millimeter-level particle surface, prepares milli-nanostructure particles, and is modified by chemical modification, prepares second-order milli-nanostructure aluminum-based particles modified by fluorosilane, and uses this as functional pigment and polymer mixed film-forming, while realizing coating super-hydrophobic performance, can also significantly improve its physical and mechanical properties. And the present invention has strong chemical interaction force between the nanostructure constructed in situ on millimeter-level particle surface and monolithic particles, is not easy to destroy separation each other, has good structural stability, and this is another advantage of the super-hydrophobic coating prepared by the present invention.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a super hydrophobic coating material, characterized in that: The method comprises the following steps: Step 1: Prepare modified milli-nanostructured metal-based particles: Use millimeter-sized metal powder particles as base particles, use a mixed solution of water, hydrochloric acid and hydrofluoric acid in a volume ratio of (80-100): (8-10): 1 to etch the metal-based particles, construct a nanostructure on the surface of the base particles, and then add them to a low surface energy solution for chemical modification; Step 2: The material obtained in step 1 is combined with an adhesive to obtain a super-hydrophobic coating material.
2. A method for preparing a super hydrophobic coating material according to claim 1, characterized in that, In the step 1, the etching time is 10 min-60 min, and after etching, the material is washed with deionized water and dried for later use.
3. A method for preparing a super hydrophobic coating material according to claim 1, characterized in that, The mass of the metal-based particles, the volume of the mixed solution and the volume ratio of the low surface energy solution are: (2-5) g: (94-125) mL: (12-20) mL.
4. A method for preparing a super hydrophobic coating material according to claim 1, characterized in that, The millimeter-sized metal powder particles in step one include at least one of millimeter-sized aluminum powder particles, millimeter-sized copper powder particles, and millimeter-sized zinc powder particles.
5. A method for preparing a super hydrophobic coating material according to claim 1, characterized in that, The low surface energy solution comprises at least one of a n-hexane solution containing trichloro 1H, 2H, 3H heptadecafluorodecylsilane, an ethanol solution containing palmitic acid, and an ethanol solution containing stearic acid.
6. A method for preparing a super hydrophobic coating material according to claim 1, characterized in that, In step 1, the millimeter-sized metal powder particles are cleaned with deionized water and anhydrous ethanol respectively, and then acid-etched.
7. A method for preparing a super hydrophobic coating material according to claim 1, characterized in that, In the step 2, the adhesive is AB glue, which is mixed in a mass ratio of 1:1 and coated with a thickness of 2 mm to 3 mm to obtain a film. The material obtained in step 1 is dispersed on the surface of the film, embedded in the film and cured for 24 hours to obtain a super-hydrophobic coating material.
8. A method for preparing a super hydrophobic coating material according to claim 1, characterized in that, The mass ratio of the material obtained in the step 1 to the adhesive is: (1.5-4):
1.
9. A super hydrophobic coating material, characterized in that: The super-hydrophobic coating material is prepared by the preparation method described in any one of claims 1-8.
Citation Information
Patent Citations
Self-adaptive microstructure antifouling anti-drag material and preparing method thereof
CN104044694A
Mixed steam condensation heat transfer reinforcement surface, preparation method and application thereof
CN108097553A
Manufacturing method for super-hydrophobic anti-icing surface with millimicro-nano three-stage structure, and application of manufacturing method
CN111906993A
Resistance-reducing material with lubricating layer and super-hydrophobic layer and preparation method of resistance-reducing material
CN115519235A
Methods for fabricating isolated micro- and nano- structures using soft or imprint lithography
SG123152A1